Lebanon Economic Monitor, Fall 2013 : The Brunt of the Syrian Conflict - World Bank (Washington, DC, 2015)
The Lebanon Economic Monitor provides an update on key economic developments and policies over the past six months. It also presents findings from recent World Bank work on Lebanon. It places them in a longer-term and global context, and assesses the implications of these developments and other changes in policy on the outlook for Lebanon. This report discusses the following: a) Spillovers from the Syrian conflict are imposing a heavy toll on Lebanon’s economy which, under an unchanged environment, is projected to grow by 1.5 percent in both 2013 and 2014. b) The economic slowdown and domestic and regional turmoil also affected banking activity. c) After a strong fiscal expansion in 2012, the fiscal deficit continues to widen in 2013, to a large extent driven by the spillovers from the Syrian conflict. d) The balance of payments strengthened during the first seven months of 2013, in part due to the weakening economic activity and sustained capital inflows. e) The conflict in Syria is having a large, negative, and rapidly growing impact on Lebanon’s economy, its social fabric, and its public services (Special Focus).